Basic Sanitation Factors and Clean and Healthy Living Behavior as Determinants of Stunting: A Case Study in Bondowoso - Wibasusanti, Gilang Putri; Thohari, Imam; Winarko; Wardoyo, Iva Rustanti Eri; Sulistijowati; Laksono, Cahyo Widoko (Public Health Research Development, 2024)
Stunting is a nutritional problem that remains high in Indonesia, especially in rural areas like Bondowoso. Poor basic sanitation and bad implementation of Clean and Healthy Living Behavior are often associated with stunting in children under five. This study aims to analyze the relationship between basic sanitation factors and Clean and Healthy Living Behavior as a determinant of stunting in the working area of Sempol Community Health Center in 2024. This research used a case-control study methodology in conjunction with observational analytics. The samples were houses with stunting and non-stunting toddlers in the working area of Sempol Community Health Center. The samples are 24 for each group, using a systematic random sampling technique from a population of 925 toddlers. Data analysis using the Chi-square test with 0.05 degree of error. The result of this research showed that there are differences in basic sanitation facilities of houses and Clean and Healthy Living Behavior in stunting and non-stunting toddlers in the working area of Sempol Community Health Center in 2024. Basic sanitation and Clean and Healthy Living Behavior factors are important factors in efforts to prevent stunting. Improving access to sanitation and promoting the Clean and Healthy Living Behavior program must be a priority in the Public Health Intervention Program in Bondowoso.